OP83 Diet and physical activity-based weight management programmes for adults: re-analysis of a systematic review through the lens of user views to identify pathways to effectiveness. (2nd September 2017) - Melendez-Torres, GJ; Sutcliffe, K; Burchett, HED; Rees, R; Richardson, M; Thomas, J
Abstract : Background: Previous systematic reviews of weight management programmes have not been able to account for heterogeneity of effectiveness within programmes using top-down behavioural change taxonomies and standard meta-regression methods. This could be due to the complex nature of these interventions, the intersecting aspects of different intervention components, and the presence of overlapping causal pathways to effectiveness (or lack of effectiveness). Qualitative comparative analysis is a method that, when used in the synthesis of complex interventions, can help identify the 'how' and 'why' of intervention effectiveness while accounting for these overlapping and intersecting causal pathways. Methods: We updated a previous systematic review of studies relating to the views of programme users and trials of weight management programmes in adults that included dietary and physical activity components. We thematically analysed views studies to identify intervention features perceived to be important by service users and providers. We selected the most and least effective trials as measured by amount of weight loss at 12 months compared to minimal treatment. Using intervention components suggested by the synthesis of user views, we labelled interventions as to the absence or presence of these components and, using qualitative comparative analysis, we identified combinations of components that created the conditions sufficient for interventions to be most effective and least effective. Results: Our analysis included 21 studies of user views reported in 26 papers, and 20 interventions—10 most effective and 10 least effective—reported in 15 trials. The synthesis of user views suggested three facets of interventions for analysis: provider-user alliance, or the quality of the relationship between users and providers; provider directiveness, or the perceived high need for guidance from providers; and group relationships, or the quality of the relationship between peers in weight management programmes. Across our analyses, we found that pathways to intervention effectiveness were characterised by the presence of opportunities to develop supportive relationships with providers or peers, clear direction from providers together with components to develop self-regulation of exercise and dietary behaviour. Discussion: Revisiting complex interventions through a lens that accounts for complexity can facilitate action on a pressing public health problem like obesity and overweight. Though QCA is an inductive method, this innovative approach has enabled the identification of neglected critical aspects of WMPs, such as the nature of relationships within them, which were previously not considered to be as important as more concrete content such as dietary focus.